Emission risk assessment of carbonaceous aerosols from road transport in the megacity of Chennai, India - S.N. Ahamed Ibrahim; A. Ramachandran; S. Pavithrapriya; K. Palanivelu (Atmospheric Environment: X)
On-road vehicular emissions constitute a substantial source of air pollution within densely populated metropolitan areas, giving rise to substantial concerns related to public health and environmental integrity. This study analysed Particulate Matter (PM2.5), Black Carbon (BC) and Organic Carbon (OC) emission inventory observed trends from 2003 to 2020 and projected trends up to 2070 under different e-vehicle usage rate scenarios in Chennai City. Based on the projected vehicular growth rate, the annual inventory of PM2.5 could peak at 17 Gg in 2035, a 112 % increase from 2020 levels. Likewise, the BC and OC would increase at 6.5 Gg and 5.3 Gg, respectively. Also, compared to conventional fossil fuels at the end of 2040, pollution inventory would decrease by approximately 43 %, 66 %, 85 %, and 100 % under low (2 %/yr), medium (3 %/yr), high (4 %/yr), and very high (5 %/yr) usage rate scenarios for electric vehicles. The study also predicts emission intensity disparities in various traffic conditions across the city, highlighting the urgent need for transitioning to electric vehicles and targeted interventions in congested areas. The core city, particularly zones like Royapuram, Valasaravakkam, and Tondiarpet, exhibits severe emission risk, driven by key indicators such as population, bus stops, road density, omnibus, heavy vehicle flow, and congested traffic conditions. The outcome of this study underscores timely action is needed to address the projected rise in vehicular emissions and associated health burdens in fast-growing megacities like Chennai. The study provides critical insights for policymakers to mitigate air pollution through targeted interventions.